State Universityâs Institusional Repository as a Storage for Civitas Academia Intelectual Property - Srirahayu, Dyah Puspita (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2015)
Many works - works the academic community that has not been published so that the intellectual property of an educational institution is not widely known by the general public. Institutional repository created and used to manage the results of these works that can be accessed by all people. This study aimed to describe the institutional repository of high perguruang country in Java Timursebagai container to the intellectual academic community views of content, the software used unit that houses, and ratings on Webometrik. This study uses a quantitative approach with descriptive methods. The population used in this study are all the institutional repository of public universities in East Java, which already are online. The sampling technique is the total sampling. The results of this study found that 50% of state universities in East Java has an IR that can be accessed via the internet, 100% of existing IR content is scientific output, the software used various existing GDL, DSpace, Eprints and others, and IR state universities in Java East 66.7% was ranked in webometrik